2021
DOI: 10.1186/s12884-020-03503-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with preterm birth at Wachemo University Nigist Eleni Mohammed memorial hospital, southern Ethiopia: case-control study

Abstract: Background Preterm birth is defined as the birth of a baby before 37 completed weeks of gestation. Worldwide, prematurity is the second foremost cause of death in children under the age of 5 years. Preterm birth also gives rise to short and long term complications. Therefore, the primary aim of this study was to identify the factors associated with preterm birth in Wachemo University Nigist Eleni Mohammed Memorial referral hospital, Hadiya Zone, Southern Ethiopia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Other reported sociodemographic factors included low socio-economic class [ 86 , 108 ], limited maternal education (only primary or no education) [ 77 , 95 , 104 , 106 ], rural residence [ 27 , 30 , 48 , 50 , 81 , 106 ], employment [ 41 , 86 ], Muslim mothers [ 41 ], mothers who had fear of delivery [ 41 ], and mother’s exposure to unfavourable working conditions including stressful jobs [ 41 ], exposure to vibration [ 12 ], and carrying heavy loads [ 24 ] which were all reported to increase the risk of PTB. Additionally, in 6 of the included studies [ 30 , 31 , 34 , 39 , 58 , 86 ], unmarried mothers had increased odds of having PTB compared to their married counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other reported sociodemographic factors included low socio-economic class [ 86 , 108 ], limited maternal education (only primary or no education) [ 77 , 95 , 104 , 106 ], rural residence [ 27 , 30 , 48 , 50 , 81 , 106 ], employment [ 41 , 86 ], Muslim mothers [ 41 ], mothers who had fear of delivery [ 41 ], and mother’s exposure to unfavourable working conditions including stressful jobs [ 41 ], exposure to vibration [ 12 ], and carrying heavy loads [ 24 ] which were all reported to increase the risk of PTB. Additionally, in 6 of the included studies [ 30 , 31 , 34 , 39 , 58 , 86 ], unmarried mothers had increased odds of having PTB compared to their married counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of or underutilization of antenatal care (ANC) was by far the most reported obstetric risk factor associated with PTB. Twenty-six of the included studies [ 9 , 18 , 19 , 22 , 23 , 25 , 29 , 30 , 36 , 37 , 39 , 41 , 48 , 50 , 52 , 58 , 60 , 62 , 71 , 74 , 76 , 86 , 90 , 97 , 104 , 106 ] reported that pregnant mothers with fewer (<4 ANC visits) or with no ANC visits were more likely to have a PTB. In one study that compared the prevalence of PTB among mothers who had one, two, three or four ANC visits, the prevalence decreased with an increase in number of ANC visits (21.6%, 22.3%, 17.5% and 5.6%, respectively) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, expectant treatment is an important treatment for patients with PPROM. However, prolonged latency period increases the risk of ascending reproductive tract infection, which might lead to intrauterine infection [ 10 ]. Obstetrical strategies to treat patients with PPROM remain controversial, and the optimal delivery time is unclear [ 1 ], which depends on an evaluation of the risks and benefits of attempted pregnancy prolongation compared with expeditious delivery [ 11 ].…”
Section: Introductionmentioning
confidence: 99%